Black salt queen - Bansil, Samantha (Letters from Maynara, 2025)
"There can be no victory without betrayal. Hara Duja Gatdula, queen of the island nation of Maynara, holds the divine power to move the earth. But her strength is failing and the line of succession gives her little comfort. Her heir, Laya, is a danger--a petty and passionate princess who wields the enormous power of the skies with fickle indifference. Circling the throne is Imeria Kulaw--the matriarch of a traitorous rival family who wields recklessly enhanced powers of her own--with designs to secure a high-ranking position for her son and claim the crown for her family. Each woman has a secret weakness--a lover, a heartbreak, a lie. But each is willing to pay the steepest price to bring down her rivals once and for all. Filled with passion, romance, betrayal, and divine magic, Black Salt Queen journeys to a gorgeous precolonial Philippines-inspired island nation where women--and secrets--reign." -- Back cover.